Circadian rhythm disruption: health consequences. Issue 2 (3rd March 2016) - Sharma, Arpita; Tiwari, Shashank; Singaravel, Muniyandi
Abstract : Circadian rhythms control many facets of biology and their disruption can be associated with severe pathological conditions. In healthy individuals, disturbances to the sleep-wake cycle can be the root cause of many problems. In the present review, we explore the major factors contributing to circadian rhythm disruption, including sleep disorders, jet lag, and shift work. The consequences of these disruptions on central and peripheral clocks and the important areas of the body controlled by them involve immune function and metabolism, as well as alterations in cognitive abilities, thereby impairing social and occupational behavior. Further work exploring clock genes, light exposure, and cellular changes will be critical for identifying how these factors interact to affect health and behavior.